Insulin Secretory Defect and Insulin Resistance in Isolated Impaired Fasting Glucose and Isolated Impaired Glucose Tolerance. (15th December 2015) - Aoyama-Sasabe, Sae; Fukushima, Mitsuo; Xin, Xin; Taniguchi, Ataru; Nakai, Yoshikatsu; Mitsui, Rie; Takahashi, Yoshitaka; Tsuji, Hideaki; Yabe, Daisuke; Yasuda, Koichiro; Kurose, Takeshi; Inagaki, Nobuya; et al.
Abstract : Objective. To investigate the characteristics of isolated impaired glucose tolerance (IGT) and isolated impaired fasting glucose (IFG), we analyzed the factors responsible for elevation of 2-hour postchallenge plasma glucose (2 h PG) and fasting plasma glucose (FPG) levels. Methods. We investigated the relationship between 2 h PG and FPG levels who underwent 75 g OGTT in 5620 Japanese subjects at initial examination for medical check-up. We compared clinical characteristics between isolated IGT and isolated IFG and analyzed the relationships of 2 h PG and FPG with clinical characteristics, the indices of insulin secretory capacity, and insulin sensitivity. Results. In a comparison between isolated IGT and isolated IFG, insulinogenic index was lower in isolated IGT than that of isolated IFG (0.43 ± 0.34 versus 0.50 ± 0.47, resp.;p < 0.01 ). ISI composite was lower in isolated IFG than that of isolated IGT (6.87 ± 3.38 versus 7.98 ± 4.03, resp.;p < 0.0001 ). In isolated IGT group, insulinogenic index showed a significant correlation with 2 h PG (r = - 0.245, p < 0.0001 ) and had the strongest correlation with 2 h PG (β = - 0.290 ). In isolated IFG group, ISI composite showed a significant correlation with FPG (r = - 0.162, p < 0.0001 ) and had the strongest correlation with FPG (β = - 0.214 ). Conclusions. We have elucidated that decreased early-phase insulin secretion is the most important factor responsible for elevation of 2 h PG levels in isolated IGT subjects, and decreased insulin sensitivity is the most important factor responsible for elevation of FPG levels in isolated IFG subjects.